2010
DOI: 10.4314/ajbr.v10i3.50632
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for entry into the medical programme of nigerian universities: the efficacy of combining school certificate results with jamb scores in selection of candidates into the ogbomosho medical school

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Our finding about lack of significant association between UME and undergraduate performance is consistent with similar studies (Afolabi et al, 2007;Adeniyi et al, 2010) conducted in other universities within Nigeria, but contradicts with others (Afolabi et al, 2007a;Ajaja, 2010;Osakuade, 2011;Igwe and Adiku, 2012). This contradiction is probably because these studies investigated students from only one programme (Afolabi et al, 2007a) or one department (Ajaja, 2010; Igwe and Adiku, 2012) and did not correct for gender (Afolabi et al, 2007a;Ajaja, 2010;Osakuade, 2011;Igwe and Adiku, 2012 Oyebola, 2006;Obioma and Salau, 2007;Afolabi et al, 2007;Adeniyi et al, 2010). This could be explained by the fact that these groups, as noted before, investigated only one programme of study or did not correct for gender.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our finding about lack of significant association between UME and undergraduate performance is consistent with similar studies (Afolabi et al, 2007;Adeniyi et al, 2010) conducted in other universities within Nigeria, but contradicts with others (Afolabi et al, 2007a;Ajaja, 2010;Osakuade, 2011;Igwe and Adiku, 2012). This contradiction is probably because these studies investigated students from only one programme (Afolabi et al, 2007a) or one department (Ajaja, 2010; Igwe and Adiku, 2012) and did not correct for gender (Afolabi et al, 2007a;Ajaja, 2010;Osakuade, 2011;Igwe and Adiku, 2012 Oyebola, 2006;Obioma and Salau, 2007;Afolabi et al, 2007;Adeniyi et al, 2010). This could be explained by the fact that these groups, as noted before, investigated only one programme of study or did not correct for gender.…”
Section: Discussionsupporting
confidence: 81%
“…CGPA (Adeyemo and Gbemisola, 2006, Afolabi et al, 2007, 2007aAdeniyi et al, 2010) or final year CGPA (Bamidele and Odusola, 2006;Obioma and Salau, 2007). However, we used both the first and final year CGPA, which enabled us to see if the association between the entrance exams and academic performances in the University stayed the same in the first or final year.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Nigeria adopted centralized university admission through the establishment of the Joint Admission and Matriculation Board (JAMB) administered by individual universities. The validity of these selection processes were studied by several authors who independently concluded that the combination of UTME and SSCE effectively predicted academic success in the first two years of medical education, and that the school's certificate 45,46 scores were better predictors of success.…”
Section: Sub-saharan Africa (Kenya Nigeria and South Africa)mentioning
confidence: 99%